Flexural behaviour of reinforced concrete beam with circular web opening - Nur Izzah, Mohd Nasri (2017)
The openings in the beams building are necessary for the passage of utility ducts. This study was conducted to investigate the flexural behaviour of reinforced concrete beams with circular web opening. In this investigation, 4 beams using G30 concrete were cast and tested. A solid control beam was used as the reference for comparison with other beams with an opening. The sizes of the openings considered in this study included ∅60 mm, ∅80 mm and ∅100. All the beam specimens had a cross-section of 200 mm x 150 mm and a total length of 2000 mm. The beams were tested under three-point bending until failure. The increase of the diameter of the opening in beams with opening causes the change in the pattern of cracks. Besides that, with an increase in the opening diameter, the ultimate load of the beam reduces with an increase in deflection. Reduction of a portion of the concrete area in the beam reduces the strength of the beam thus causing beam to fail with lower load.